Cutaneous pili migrans in two infants - Lin CUI; Bingxin XIE; Zhuo ZHAO; Shifa ZHANG (editoiral office of Journal of Diagnosis and Therapy on Dermato-venereology, 2022)
Two cases of cutaneous pili migrans were reported. Case 1 was a female patient, aged 1 years and 11 months. She presented with pain in the sole of her right foot for 1 day. Dermatological examination: there was a black punctured skin lesion on the medial and lateral edge of the right paw. Magnifying glass showed that a black hair-like substance penetrated deep into the skin, and the residual end was visible on the skin surface. After being extracted with sharp tweezers, it was found to be a hard black broken hair with a length of about 4 mm. No hair follicle was found, so local disinfection was carried out. Lately, many similar hairs on her bed were found. Case 2 was a male patient, aged 4 years and 2 months. He went to the hospital because of left paw pain for 1 month. Dermatological examination: there was a black skin lesion near the heel of the left paw. Under magnifying glass, the hair was curled in the skin and the end was free from the skin surface. A black broken hair about 6 mm long was found with tweezers. No hair follicle was found. Lately, many similar hairs were also found on his bed. It was considered that the onset of the 2 patients was caused by adult hair shedding on the bed, and the patient's barefoot contact was followed by stabbing into the skin of the sole of the foot.